FENOMENA SIKAP BERBAHASA DI INDONESIA - Heri Kustomo (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Abstract: The attitude simply can not be observed directly. However, the attitude will encourage someone to follow language act. As citizens of Indonesia we have a moral responsibility to be proud of the Indonesian. Reality in the public turned out to indicate another. Global society is difficult to avoid the attitude of violations of the rules of the Indonesian. We too hard to avoid any language act that birth code switching and interference code. Attitude of man that are easy going, more practical, more cool, more prestigious, and indifference to the rules of the official languages of various groups such as: state officials, journalists, reporter, artist , celebrities and community leaders participate and influence the attitude of the public speaking. Moreover the language of the celebrities who are very close to the world of entertainment television and became a teen idol will have a very large role in encouraging the attitude of teenagers to imitate the language they use. However our language is Indonesian. Therefore we must seek for our society, including the teenagers learn to be consistent in principle the Indonesian. Only with prouding to national language of our nation, the existence of Indonesian can be maintained.